2022
DOI: 10.1016/j.habitatint.2022.102517
|View full text |Cite
|
Sign up to set email alerts
|

Are leading urban centers predisposed to global risks- An analysis of the global south from COVID-19 perspective

Abstract: COVID-19 initially spread among prominent global cities and soon to the urban centers of countries across the globe. While cities are the hotbeds of activities, they also seem highly exposed to global risks including the pandemic. Using the case of COVID-19 and World Risk Index framework, this paper examines if the leading cities from the global south are inherently vulnerable and exposed to global risks and can they exacerbate the overall risk of their respective nations too. Compared against their respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 71 publications
0
9
0
1
Order By: Relevance
“…The impact of public health responses to the pandemic articulated themselves in additional stress, anxiety, loneliness, social isolation, economic difficulties and overcrowding amongst many private and social renters ( Byrne & Mcardle, 2022 ). The magnitude of these effects or the ways of experiencing them vary depending on the social environment ( Shekhar et al, 2022 ). Notwithstanding these impacts, COVID-19 did not per se affect the social or economic foundations of private or social renting as institutions.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of public health responses to the pandemic articulated themselves in additional stress, anxiety, loneliness, social isolation, economic difficulties and overcrowding amongst many private and social renters ( Byrne & Mcardle, 2022 ). The magnitude of these effects or the ways of experiencing them vary depending on the social environment ( Shekhar et al, 2022 ). Notwithstanding these impacts, COVID-19 did not per se affect the social or economic foundations of private or social renting as institutions.…”
Section: Introductionmentioning
confidence: 99%
“…The remainder of the rural areas and other sparse settlements in the countryside had less than 34 cases per 1000 population. A study by [ 38 ] also found that urban centers of the global south were highly likely to be predisposed to global risks such as COVID-19 because of their vulnerability and exposure, exacerbated by the process of urbanization in those centers. In Eswatini, urban centers are the backbone of daily activities and daily commuting between rural and urban centers is not uncommon.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the COVID-19 pandemic serves as a valuable lesson to critique aspects of decentralization in regards to urban agglomerations and development. Urban agglomerations in the global south still facing governance challenges of regional disparity, specifically a significant capacity gap between the core region and its surrounding districts [ [37] , [38] , [39] ]. Most urban centers in Asia, including Indonesia, have grown beyond its administrative boundaries, expanding without corresponding public services in peri-urban areas [ 15 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%